Large yellow croaker (Lrimichthys crocea) IL-2 modulates humoral immunity via the conserved JAK-STAT5 signal pathway. Issue 133 (February 2023) - Mu, Pengfei; Teng, Yan; Wu, Hanyu; Li, Xinran; Huo, Jieying; Ao, Jingqun; Chen, Xinhua
Abstract: The terminal differentiation of B cells into plasma cells is central to the generation of protective, long-lived humoral immune responses. In mammals, interleukin-2 (IL-2) has been shown to play a role in B cell proliferation and differentiation. However, it remains unclear whether fish IL-2 is involved in B cell proliferation and differentiation. To this end, we investigated the regulatory role of IL-2 in B cell proliferation and differentiation in large yellow croaker ( Larimichthys crocea ). We found that L. crocea IL-2 ( Lc IL-2) significantly increased IgM + B cells proliferation both in vivo and in vitro and facilitated IgM + B cells differentiation into plasma cells. Furthermore, Lc IL-2 increased the production of specific antibodies after immunization with the Vibrio alginolyticus subunit vaccine, recombinant dihydrolipoamide dehydrogenase (rDLD); simultaneous administration of Lc IL-2 and rDLD prior to challenge with Vibrio parahaemolyticus or V. alginolyticus significantly increased relative percent survival. Mechanistically, Lc IL-2 promoted B cell proliferation and regulated B cell differentiation by triggering the JAK-STAT5 signaling pathway. Collectively, our results demonstrated that Lc IL-2 improved B cell proliferation and specific antibody production via the conserved JAK-STAT5 signaling pathway in large yellow croaker, providing valuable insights into the mechanisms underlying the IL-2-mediated regulation of the humoral immune response in fish. Highlights: Lc IL-2 facilitates IgM + B cells proliferation and differentiation into plasma cells. Lc IL-2 improves specific IgM production and immunoprotective efficacy of vaccine. Lc IL-2 regulates B cell proliferation and differentiation via JAK-STAT5 signaling.